Visible Light-Driven Gas-Phase Artificial Photosynthesis Reactions over Ruthenium Metal Nanoparticles Modified with Anatase TiO2. (30th April 2019) - Morais, Eduardo; O'Modhrain, Colin; Thampi, K. Ravindranathan; Sullivan, James A.
Abstract : Ruthenium metal nanoparticles with a narrow size distribution have been synthesised via a solvothermal method. The solids were characterised using a range of analytical techniques (XRD, TEM, TPD, and XPS) and tested in the CO2 +H2 O reaction under simulated solar radiation, showing photocatalytic activity towards the production of CH4 and CO. The photocatalysis was promoted through a plasmonic excitation of the Ru. The addition of Ti to the preparation resulted in the formation of anatase TiO2 . Notwithstanding the fact that the energy of the light used during the photocatalysis was insufficient to excite TiO2, its presence affects the catalysts' optical and chemical properties and the product (CH4 /CO) ratios, favouring the evolution of CO over that of CH4 (suggesting exciton transfer to TiO2 from plasmonically excited Ru).